A Study on Level of Patient Satisfaction Towards Multi- Speciality Hospital Services (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Patient satisfaction is an important measure of the quality of care provided by health care organisations. It is not only important for gaining insights into the perception of the patient’s on the delivery of the health care service, but also a key outcome of care. The present study was undertaken to identify the factors in which the patients are satisfied by the services offered by the multi- speciality hospitals in Coimbatore city. The objective of the study states to examine the level of patient satisfaction towards hospital services. primary data was collected from 120 respondents using a well-structured questionnaire through google form. The data collected through questionnaire were analysed. The research methodology employed in this study includes percentage analysis, Garrett ranking and Chi- square test. It was found that the majority of the respondents choose Kovai medical center and hospital to undergo the treatment towards multi- speciality hospitals. Most of the respondent’s nature of treatment is towards medical. It was suggested that the hospital management should increase the physician referral centers, complaint handling and service recovery systems should be strengthened to enhance effectiveness of multi- speciality hospital services. It was concluded as the competition is increasing, the hospitals are making their best efforts to provide quality healthcare services to its customers.